Evaluation of System Development Projects - Munk-Madsen, Andreas (DAIMI Report Series, 1986)
Many groups are involved in system development projects: System development management, system developers, user management, and users. All of them wish to influence the project. Influence, however, requires understanding. The process of obtaining this understanding is called project evaluation. This report will discuss project evaluation. The most important conclusions are: Evaluation should not be seen as an appendage to planning, but as a complementary activity. There are two fundamentally different kinds of project evaluation. There are two types of documents constituting the key for understanding most system development projects. In practice evaluation of system development projects requires the active participation of the system developers.